Intersectionality at the Heart of Oppression and Violence against Women - Julie George (Journal of Moral Theology, 2023)
Diverse biases contribute to how society perceives survivors of sexual violence and domestic violence, and stereotypes often create obstacles for extending support and care. Intersectionality helps explain how all victims of violence are not treated the same way and the complexities of multiple arenas of oppression and privilege in our society. In particular, victims of sexual violence are too often subject to exploitation and harassment within the justice system when due process of law is emphasized over protection of victims. For Dalit women in Indian society, the very systems and movements that should safeguard them have become instruments of their marginalization. These case studies will examine the way intersectional oppression operates within India’s social and legal systems leading to further oppression of Dalit women. It is imperative that stringent provisions and measures addressing gender-based violence, intersectional violence, sexual abuse, caste, race and class-based oppression and other marginalities faced by women feature as essential elements of all our systems, policies and decisions.